2009
DOI: 10.1002/bit.22591
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic flux responses in riboflavin overproducing Bacillus subtilis to increasing glucose limitation in fed‐batch culture

Abstract: How do intracellular fluxes respond to dynamically increasing glucose limitation when the physiology changes from strong overflow metabolism near to exclusively maintenance metabolism? Here we investigate this question in a typical industrial, glucose-limited fed-batch cultivation with a riboflavin overproducing Bacillus subtilis strain. To resolve dynamic flux changes, a novel approach to (13)C flux analysis was developed that is based on recording (13)C labeling patterns in free intracellular amino acids. Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…Cell metabolisms are highly dependent on environmental conditions, so the metabolic state often shifts during the cultivation period [1], [2], [3]. Characterizing the transience of metabolic fluxes is important for understanding how cells responded to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Cell metabolisms are highly dependent on environmental conditions, so the metabolic state often shifts during the cultivation period [1], [2], [3]. Characterizing the transience of metabolic fluxes is important for understanding how cells responded to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…This result confirms that the FAAs-based method can reduce labeling time for MFA. Although the faster turnover rate for FAAs is preferable for an MFA study of batch and fed-batch culture [12,13,14,15], it remains unclear whether a reliable result can be produced by FAAs-based MFA. It is not also obvious which FAAs are reproducibly observed from E. coli cells in various culture conditions, and whether a precise metabolic flux can be estimated by using the observed amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…For the MFA study of batch and fed-batch culture, intracellular free amino acids (FAAs) with faster turnover rates are more promising targets for a 13 C enrichment measurement [12,13,14,15,16]. The time course analysis of 13 C enrichment of FAAs demonstrated that the experimental time required to reach an isotopic steady state of the FAAs is 2 to 10 times faster than that for PAAs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the biotechnology industry, non-stationary 13 C-metabolic flux ratio analyses via isotopic tracing have obtained the snapshots of the metabolic fluxes through several key nodes in B. subtilis [108]. Time-dependent fluxomics has also been proposed to investigate B. subtilis fermentation processes [110]. …”
Section: Application Of Isotope-assisted Metabolomicsmentioning
confidence: 99%